1981
DOI: 10.1136/bjsm.15.3.172
|View full text |Cite
|
Sign up to set email alerts
|

Blood lactate concentration following maximum exercise in trained subjects.

Abstract: The time when blood lactate reaches peak concentration following maximum exercise is unclear. The post exercise venous blood lactate concentration was determined serially for 30 minutes in 13 trained men following maximum exercise on a motor driven treadmill. Lactates were determined enzymatically in duplicate. The VO2 max and percent body fat was 65.1 +/- 4.8 ml.kg-1.min-1 and 11.4 +/- 1.4, respectively. The venous lactate reached a peak concentration at the 6th minute (14.2 mmol.L-1) of an inactive recovery,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
2

Year Published

1984
1984
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 18 publications
2
17
0
2
Order By: Relevance
“…Our results were similar to other authors studying single-device exposures 10. In a study by Gass et al,11 venous lactate increased to 14.2 mmol/L after a maximal exercise regimen on a treadmill in trained subjects. The changes in lactate in our study are small by comparison.…”
Section: Discussionsupporting
confidence: 92%
“…Our results were similar to other authors studying single-device exposures 10. In a study by Gass et al,11 venous lactate increased to 14.2 mmol/L after a maximal exercise regimen on a treadmill in trained subjects. The changes in lactate in our study are small by comparison.…”
Section: Discussionsupporting
confidence: 92%
“…A mean BLC-max of 14-16mmol•L -1 in all time-trials indicated that they were performed with maximal effort 27 and the decrease in MVC indeed confirmed the presence of muscle fatigue. The present paper also demonstrated that both peripheral and central mechanisms contributed to muscle fatigue in all time-trials.…”
Section: Discussionmentioning
confidence: 84%
“…Exercise heart rates were ascertained by cardiometer (Cardionics) and lung capacities by wedge spirometer (Vitalograph). Capillary blood samples (50 pl) were obtained by pin prick at 20 second intervals during continuous running, and at two and five minutes post-test, to ascertain lactate inflection point [4 mmol.F1 I (Mader et al, 1976) and post-exercise lactate levels (Gass et al, 1981). Samples were subsequently assayed in duplicate according to the methods of Guttman and Wahlefeld (1974).…”
Section: Methodsmentioning
confidence: 99%